An epidemiological study of paediatric motocross injuries in the United Kingdom. (October 2015) - Singh, Rohit; Malhotra, Akshay; Kyle, Nigel; Hay, Stuart
Purpose: Although off-road motorcycling is one of the most popular sports activities practised by millions of people worldwide, little has been written on motocross injuries and their prevention. In the UK alone, motocross has grown into a phenomenally ambitious and popular franchise. There are >200 motocross clubs across the country holding >900 events annually. The aim of this study is to categorise and quantify the magnitude of motocross paediatric injuries and associated morbidity. Methods: Data were collected prospectively over 4 years (2010−2014) at our unit. All injuries caused by motocross biking that were referred to our trauma and orthopaedic department were included in this study, regardless of whether the rider was performing the sport competitively or recreationally. Results: During the study period, 130 patients (aged 4−17 years) were identified with a total of 142 injuries, ranging from one to six injuries per patient. Most of the injuries were sustained within the early spring and summer months, representing the start of the motocross season; 76 patients required hospital admission, with 60 (42 %) requiring surgical intervention. Conclusion: We present the first epidemiological study of motocross paediatric injuries in the UK. The results from this study highlight the frequency and severity of motocross-related injuries in the paediatric population in the UK. This may assist in providing recommendations and guidelines to governing bodies and to parents. The injuries sustained during motocross have significant resource implications, especially for smaller rural hospitals, as shown by the number of injuries doubling over the past 4 years.